Chronic invasive fungal sinusitis: characterization and shift in management of a rare disease. Issue 12 (27th July 2016) - D'Anza, Brian; Stokken, Janalee; Greene, J. Scott; Kennedy, Thomas; Woodard, Troy D.; Sindwani, Raj
Abstract : Background: Chronic invasive fungal sinusitis (CIFS) is a rare subtype of mycotic diseases involving the paranasal sinuses. It is characterized by a slow onset and invasive organisms with non‐granulomatous inflammation seen on histopathology. Historically, treatment has involved radical surgical resection. The purpose of this study was to describe the presentation, comorbidities, and role of more conservative treatment options. Methods: This is a multi‐institutional retrospective case series of 6 patients with CIFS over 15 years. Patients' medical comorbidities, imaging results, operative procedures, pathological findings including organisms identified, antimicrobial medications used, and outcomes were reviewed. Results: The mean time from onset of symptoms to diagnosis was 6 months. Cultures and fungal PCR identified Aspergillus species in every case. All 6 patients were found to have systemic comorbidities, with many being diabetic. Imaging findings ranged from thickening of sinus mucosa to invasion of the orbit and skull base. Treatment included long‐term antifungal therapy and conservative endoscopic surgery in all but 1 patient, who had an open approach. Every patient was free of invasive fungal disease at last follow‐up, with a range of 1 to 27 months. Conclusion: CIFS is an insidious disease often with months between symptom onset and diagnosis. It is differentiated from chronic granulomatous invasive fungal sinusitis (CGIFS) by a lack of granulomas on histopathology and an association with diabetes mellitus. Endoscopic debridement combined with long‐term oral voriconazole was an effective treatment strategy in this series.